Prevalence of Hypogonadism in β-Thalassemia Major Patients from Gaza Strip - Hamed, Amin; Zughbur, Mohammed; Shaheen, Elham (Jordan Journal of Pharmaceutical Sciences, 2021)
This study was conducted to determine the prevalence of hypogonadism among β-Thalassemia Major (β-TM) adolescent patients, and the role of iron chelation therapy (ICT) in its prevention. Data was collected from 60 β-TM patients and 35 controls aged 13─ 30 years through a questionnaire and a review of medical history to collect sociodemographic characteristics, transfusion regimen, chelating history and pubertal status. Complete blood count, serum ferritin, and pituitary-gonadal function tests were analyzed 1–2 weeks after blood transfusion. Logistic regression, independent t-test, and chi-square test were used to analyze our results and the significance was tested at p≤ 0.05. The overall prevalence of hypogonadism among β-TM patients was 75%, the mean of serum ferritin was 6704.83± 2849 ng/ml and all patients had serum ferritin above 2000 ng/ml indicating a severe iron overload. Low hemoglobin level (p=0.006), high ferritin level (p=0.018), high blood transfusion per year (24-blood transfusions) (p=0.007), and poor compliance to iron chelation therapy programs (p=0.001), were detected had significant partial effect in hypogonadism. In conclusion, hypogonadism is highly prevalent among Gaza strip β-TM patients. Its presence being associated with lower hemoglobin values, iron overload, high blood transfusion and low compliance of iron chelation therapy